Directions of Breeding of Grain Sorghum in the Lower Volga Region of Russia - Kibalnik, Oksana; Semin, Dmitry; Gorbunov, Vyacheslav; Zhuzhukin, Valery; Efremova, Irina; Kukoleva, Svetlana; Starchak, Victoria; Arhipov, Aleksey; Kameneva, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Sorghum bicolor L. Moench is a versatile crop, corn which is used for forage and fodder (for feeding agricultural animals, birds, fishes), as well as a source of raw materials for the food processing industry. Especially important is the cultivation of sorghum in the lower Volga region of Russia, characterized by frequent soil and air droughts. In “Rossorgo” scouting for earliness, high yield, improved grain quality, resistance to diseases and pests. The test sorghum genotypes were conducted at the experimental field of center “Rossorgo” in 2014–2016. All records of productivity elements of productivity and biochemical evaluation of grains are made according to standard techniques. The results of long-term work were identified and approved for use in the lower Volga region 12 varieties and 2 hybrids of sorghum. Varieties Pischevoe 35, Pischevoe 614, Кremovoe, Fakel can be used in the food industry. Grits from grain of sorghum has a higher ratio of the cooking property in comparison with cereals from other cultures. The early-maturing varieties Perspektivny 1 and Start, intended for planting with different width of spacing – 15, 45 and 70 cm were bred. Varieties of Granat, Volzhskoe 44, Avans and hybrids Irgiz, Volgar, combine high yields (5.31–10.8 t/ha) and 11.32–12.56% of crude protein in grain. Heterotic hybrids of Irgiz and Volgar are by tall (149.6 of 175.9 cm) and highest grain yield (8.02–10.8 t/ha). As raw material for starch varieties recommended Avans, Volzhskoe 44, Sarmat, Perspektivny 1, Geliofor, Volzhskoe 4, Topaz and hybrid Volgar with content in grain starch 72.31–75.60%. New varieties (Azart, Geliofor, Magistr, Bogdan, Bakalavr, Granat) characterized by a high content of starch (71.47–74.50%) and medium protein (the 11.04–12.59%), pass state testing. Thus, “Rossorgo” offers a farmer a range of cultivars and hybrids of grain sorghum, allowing the obtaining stable yields of grain and extending the use of culture in the region.